2012
DOI: 10.4049/jimmunol.1101592
|View full text |Cite
|
Sign up to set email alerts
|

Human CD90 Identifies Th17/Tc17 T Cell Subsets That Are Depleted in HIV-Infected Patients

Abstract: By revisiting CD90, a GPI-anchored glycoprotein, we show that CD90 is expressed by a subset of CD4+ and CD8+ human T cells. CD4+CD90+ cells share similarities with Th17 cells because they express the Th17-specific transcription factor RORC2 and produce IL-17A. CD4+CD90+ cells are activated memory T cells that express the gut mucosal markers CCR6, CD161, and the α4 and β7 integrins. Compared with CD90-depleted CCR6+ memory Th17 cells, CD4+CD90+ cells express higher levels of IL-22 and proinflammatory cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…20 Importantly, combination antiretroviral therapy (cART) only partially restores the damaged mucosal barrier, and IL-17-producing CD4 + Th17 cells are depleted in HIV infection despite successful cART. 11,27,28 Also, CD8 + IL-17-producing cells, named Tc17 cells or mucosa-associated invariant T (MAIT) cells, have been suggested to play an important role in mucosal defense. In contrast to CD4 + Th17 cells, CD8 + Tc17/MAIT cells are considered to be a part of the innate immune system, important for mucosal integrity, and involved in the antibacterial and antifungal defense.…”
Section: Introductionmentioning
confidence: 99%
“…20 Importantly, combination antiretroviral therapy (cART) only partially restores the damaged mucosal barrier, and IL-17-producing CD4 + Th17 cells are depleted in HIV infection despite successful cART. 11,27,28 Also, CD8 + IL-17-producing cells, named Tc17 cells or mucosa-associated invariant T (MAIT) cells, have been suggested to play an important role in mucosal defense. In contrast to CD4 + Th17 cells, CD8 + Tc17/MAIT cells are considered to be a part of the innate immune system, important for mucosal integrity, and involved in the antibacterial and antifungal defense.…”
Section: Introductionmentioning
confidence: 99%
“…Lower frequencies of Th17 and Th1 cells were reported in the peripheral blood of aviremic HIV ϩ subjects on antiretroviral therapy (ART), but those of ART-naive patients were comparable with uninfected healthy subjects (9). More recently, depletion of CD4 Th17 with the CD90 marker and its imbalance relative to Treg was noted in untreated HIV-infected subjects compared to those in infected patients on ART and healthy controls (10). Partial to full recovery of Th17 responses was also observed in some patients on ART (11), although another study (12) found no difference in the frequencies of Th17 cells in the peripheral blood and colons from uninfected subjects, HIV ϩ subjects on ART, and HIV ϩ long-term nonprogressors.…”
mentioning
confidence: 97%
“…In treatment-naive patients, some researchers established that peripheral T H 17 cells, contrary to the gastrointestinal tract, are not reduced [35,42,44], whereas others confirm a reduction in these cells [45][46][47]. Antiretroviral therapy (ART)-treated patients have lower peripheral blood T H 17 cells than untreated patients [35,44,48].…”
Section: Involvement Of Ccr6 In Cellular Hiv Pathogenesis T H 17 Cellsmentioning
confidence: 99%